The effect of a crisis on trust and willingness to reform: Evidence from survey panels in Argentina and Uruguay - Alejandro Bonvecchi; Ernesto Calvo; Susana Otálvaro-Ramírez; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2022)
Does exposure to crises reduce the citizens' trust in a country's president? Are individuals willing to accept fiscal reforms and make personal economic sacrifices if it would help the country to leave the crisis faster? We take advantage of two survey panels in Argentina and Uruguay, with a first wave fielded before COVID-19 (the crisis studied here) and a second wave a year later during the pandemic. Results provide no evidence of a decline in trust after the individual's health was compromised by COVID-19. We find mixed evidence of support for higher personal sacrifices. These results are relevant for understanding how voters' experience with COVID affects their trust in the government and whether crises could be prudent times for reforms. The results highlight the importance of having multi-country panel data for evaluating the impact of crises on trust.
Keywords: D72; D91; H0; 330; Trust; Crises; Political economy; Fiscal reforms; COVID-19